Enteromorpha polysaccharide composite sunscreen film as well as preparation method and application thereof

The Ulva polysaccharide composite sunscreen prepared by in-situ electrospinning technology and nanospray technology solves the problems of insufficient durability of existing sunscreens and the damage to the skin by titanium dioxide, achieving high breathability, long-lasting sun protection and easy removal effects .

CN119157777AActive Publication Date: 2024-12-20QINGDAO UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411367906.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The water-soluble and liquid form of existing sunscreens lead to insufficient durability, which can cause skin irritation and allergic reactions, and sunscreen ingredients such as titanium dioxide can produce oxidative free radicals that can cause damage to the skin.

Method used

In-situ electrospinning technology combined with nanospray technology, the Ulva polysaccharide composite sunscreen film was prepared. The Ulva polysaccharide solution was sprayed through a nanospray device and the titanium dioxide/PVB composite micro-nanofiber membrane was formed on the skin surface through an electrospinning device to form a sunscreen film. The film can avoid damage caused by photocatalyzing free radicals.

Benefits of technology

The prepared sunscreen is waterproof, dustproof, biocompatible and highly breathable. It can firmly adhere to the skin surface, lasting sun protection and easy to remove, avoiding pore blockage and skin irritation, and maintaining excellent UV barrier efficiency and water stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119157777A_ABST
    Figure CN119157777A_ABST
Patent Text Reader

Abstract

The invention provides an enteromorpha polysaccharide composite sunscreen film as well as a preparation method and application thereof. The method comprises the following steps: S1, respectively preparing a nano spray solution containing enteromorpha polysaccharide and a spinning solution containing nano titanium dioxide particles and PVB (Polyvinyl Butyral); s2, spraying a nano spraying solution to the surface of the skin needing sun protection nursing through a nano spraying device; and S3, performing in-situ electrospinning on a titanium dioxide / PVB composite micro-nanofiber membrane on the skin surface sprayed with the nano spray solution through an in-situ electrostatic spinning device, and compounding the titanium dioxide / PVB composite micro-nanofiber membrane with the enteromorpha polysaccharide on the skin surface to form the enteromorpha polysaccharide composite sunscreen membrane. The obtained sunscreen film has water resistance, dust resistance and biocompatibility, also has high air permeability and skin adaptability, can effectively avoid damage to skin caused by free radicals generated by catalysis of a sunscreen agent titanium dioxide, can be firmly attached to the surface of the skin, can resist sunshine for a long time, is easy to remove from the skin, and has no residue and no damage to the skin after removal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cosmetics, and in particular relates to a composite sunscreen film of enteromorpha polysaccharide and a preparation method and application thereof. Background Art

[0002] The prevalence of skin cancer has increased significantly in recent decades, and the public's awareness of the potential harm of ultraviolet rays to skin health has also increased, making the use of sunscreen an indispensable part of daily skin care. Most sunscreen products on the market are liquid creams and are mostly water-soluble, which results in insufficient durability under the action of sweat and water, and also limits the breathability of the skin. In addition, the residue in sunscreen may clog the pores of the skin, and its chemical composition may cause skin irritation, leading to allergic reactions and accelerated skin aging. In addition, the ingredients of sunscreen, such as titanium dioxide, can produce oxidative free radicals, which can irritate the skin and even have phototoxicity.

[0003] In order to reduce the amount of sunscreen used and improve durability, the use of in situ electrospinning technology to prepare nano sunscreen film materials is a potential solution. In situ electrospinning technology has shown significant advantages in many fields due to its simple operation and high directional controllability. In the field of wound dressings, this technology can directly prepare nanofiber membranes on skin wounds. Its porous structure gives excellent air permeability, which helps to maintain the humidity balance of the wound environment, promote healing, and inhibit bacterial growth, reducing the risk of infection. Previous studies by our team have shown that electrospun poly-ε-caprolactone (PCL) nanofibers have good air permeability and excellent biocompatibility, suitable for wound dressings. This study also demonstrated a simple method for directly preparing fiber membranes on human skin using a portable electrospinning device, which has air permeability and mechanical properties matching those of human skin.

[0004] However, there are relatively few studies on the application of electrospinning technology in the field of sunscreen manufacturing, and its sunscreen performance needs to be studied. For example, if the commonly used titanium dioxide particles for sunscreen are directly formed on the skin surface through in-situ electrospinning to form a fiber film, although it can theoretically play a certain role in sunscreen, the free radicals generated by the photocatalytic effect of titanium dioxide will also damage the skin and cause adverse effects. Summary of the invention

[0005] In view of the above problems, the present invention aims to provide a composite sunscreen film of Enteromorpha polysaccharide and a preparation method and application thereof. The sunscreen film prepared by the method is waterproof, dustproof and biocompatible, and also has high air permeability and skin adaptability, can effectively avoid the damage to the skin caused by free radicals catalyzed by titanium dioxide, a sunscreen agent, can firmly adhere to the skin surface, provide long-term sun protection, and is easy to remove from the skin, leaving no residue after removal and not damaging the skin.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention discloses a method for preparing a Enteromorpha polysaccharide composite sunscreen film, comprising the following steps:

[0008] S1: preparing a nano spray solution containing Enteromorpha polysaccharide and a spinning solution containing nano titanium dioxide particles and PVB respectively;

[0009] S2: Spraying the nano spray solution onto the skin surface requiring sun protection care through the nano spray device;

[0010] S3: The titanium dioxide / PVB composite micro-nano fiber membrane is in situ electrospun on the skin surface sprayed with the nano spray solution through an in situ electrospinning device. The titanium dioxide / PVB composite micro-nano fiber membrane is composited with Enteromorpha polysaccharide on the skin surface to form Enteromorpha polysaccharide composite sunscreen film.

[0011] Preferably, in step S1, the nano spray solution is an aqueous solution of Enteromorpha polysaccharide, and the content of Enteromorpha polysaccharide in the aqueous solution of Enteromorpha polysaccharide is 25-50 mg / ml.

[0012] Preferably, the solvent for making the spinning solution includes anhydrous ethanol, and each 10 g of the spinning solution contains 0.5-1.0 g of PVB and 0.025-0.1 g of nano-scale titanium dioxide.

[0013] Preferably, in step S1, the spinning solution is prepared by: dissolving PVB in anhydrous ethanol, stirring uniformly at room temperature to obtain a PVB solution, then adding nano-sized titanium dioxide to the PVB solution, stirring uniformly at room temperature, and ultrasonically treating to remove bubbles in the solution to obtain the spinning solution.

[0014] Preferably, 0.5-1.0 g of PVB is dissolved in 9.0-10.0 g of anhydrous ethanol, stirred at room temperature for 1-2 h to obtain a PVB solution, and then 0.025-0.1 g of nano titanium dioxide particles are added to 10 g of the PVB solution, stirred at room temperature for 1-2 h, and ultrasonically treated for 10-20 min to remove bubbles to obtain a spinning solution; Enteromorpha polysaccharide is dissolved in deionized water at a concentration of 25-50 mg / ml, and stirred for 30 min to obtain a nano spray solution.

[0015] Preferably, the nano spray device used in step S2 is an electrostatic spray device, the distance between the nozzle of the electrostatic spray device and the skin is set at 10-20 cm, the spray voltage is 5-20 kV, and the spray time is 100-130 s.

[0016] Preferably, in step S3, the distance between the spinning nozzle and the skin is 10-30 cm, the spinning voltage is 5-20 kV, and the spinning time is 200-300 s.

[0017] The second aspect of the present invention discloses a composite sunscreen film of Enteromorpha polysaccharide prepared by the above preparation method.

[0018] Preferably, the average fiber diameter of the sunscreen film is 500±5.8 nm.

[0019] Preferably, the contact angle between the sunscreen film and the liquid is greater than 100°.

[0020] Preferably, the tensile strength of the sunscreen film is 1.3-1.8 MPa.

[0021] Preferably, the air permeability rate of the sunscreen film is ≥60 mm / s.

[0022] Preferably, the UV blocking rate of the sunscreen film is 55-60%, and after soaking, the UV blocking rate is maintained at 53-68%, and after 1 hour of UV irradiation, the UV blocking efficiency of the sunscreen film remains the same as before irradiation.

[0023] Preferably, the sunscreen film can still maintain more than 80% of its adhesion after being in situ loaded on the skin for 120 minutes.

[0024] The third aspect of the present invention discloses the application of the above-mentioned sunscreen film in the field of skin sun protection, such as replacing sunscreen cream for daily skin sun protection, or ultraviolet protection in special working environments.

[0025] The beneficial effects of the present invention are: providing a Enteromorpha polysaccharide composite sunscreen film and a preparation method and application thereof. The sunscreen film prepared by the method is waterproof, dustproof and biocompatible, and also has high air permeability and skin adaptability, can effectively avoid the damage to the skin caused by free radicals catalyzed by the sunscreen agent titanium dioxide, can firmly adhere to the skin surface, provide long-lasting sun protection, and is easy to remove from the skin, leaving no residue after removal and not damaging the skin. Specifically:

[0026] 1) This method combines in-situ electrostatic technology with nano-spray technology. First, the enteromorpha polysaccharide solution is sprayed on the skin area that needs sun protection through a nano-spray device, and then nano-scale titanium dioxide and polyvinyl butyral (PVB) are mixed and spun through an in-situ electrostatic spinning device, so that it is directly attached to the spraying position of the enteromorpha polysaccharide solution and composited with the enteromorpha polysaccharide to form a nanofiber sunscreen film. Enteromorpha polysaccharide can prevent the free radicals generated by the photocatalytic action of titanium dioxide from damaging the skin. At the same time, compared with directly blending the enteromorpha polysaccharide and titanium dioxide composite fibers, spraying the enteromorpha polysaccharide alone through nano-spray technology can ensure that the enteromorpha polysaccharide is located on the fiber surface, thereby avoiding the influence of the polymer substrate of the electrospun fiber on the release rate of the enteromorpha polysaccharide, and improving the effect of the enteromorpha polysaccharide in scavenging free radicals.

[0027] 2) Combining the excellent waterproofness of the electrospun fiber substrate PVB and the outstanding air permeability of the electrospun nanofiber membrane, the prepared sunscreen film is not only waterproof, dustproof and biocompatible, but also highly breathable and skin-adaptable, which can meet the safety requirements of sunscreen products.

[0028] 3) The charges generated during the in-situ electrospinning process contribute to the electrostatic adsorption between the nanofibers and the skin, so that the fiber film of the present invention can firmly adhere to the skin surface, ensuring the use effect. At the same time, since the sunscreen film only adheres to the skin through physical forces (such as van der Waals forces), when the sunscreen film needs to be removed, the sunscreen film of the present invention is easy to remove from the skin without leaving any residue, which can effectively avoid the problems of pore blockage and skin irritation.

[0029] 4) The sunscreen film produced by this method has excellent physical properties: extremely high air permeability, the hydrophobic angle for daily liquid contact is more than 100°, and the tensile strength is between 1.3 and 1.8MPa, which is consistent with the tensile strength of human skin and can fit the skin and stretch accordingly, and is not easy to fall off. The ultraviolet blocking efficiency of the sunscreen film after long-term ultraviolet irradiation can be consistent with that before irradiation, showing excellent light stability. In addition, after immersing it in water for 5mm, the ultraviolet blocking efficiency only decreases by about 2%, indicating that it has good water stability, and daily sweating and waterproof living environment will not affect the anti-ultraviolet effect, and long-term waterproof sun protection can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The SEM image and fiber diameter distribution statistics of the fiber material prepared in the embodiment of the present invention;

[0031] Figure 2 This is a schematic diagram of the statistical results of the liquid contact angle measured by the hydrophobicity test of Example 5;

[0032] Figure 3 This is a graph showing the test results of the fiber tensile properties of Example 5;

[0033] Figure 4 This is a graph showing the air permeability test results of Example 5;

[0034] Figure 5 The fluorescence in vivo imaging photo and fluorescence intensity change curve of Example 6;

[0035] Figure 6 The optical microscope photographs of the skin surface before and after the sunscreen film of Example 7 is removed;

[0036] Figure 7 This is a graph showing the UV blocking rate test results of Example 8;

[0037] Figure 8 The particle blocking rate and pressure drop test result diagram of Example 9;

[0038] Fig. 9 is a diagram showing the cell compatibility assessment results of Example 10;

[0039] Fig.10 This is a graph showing the results of an animal experiment on the ultraviolet shielding performance of the sunscreen film of Example 11;

[0040] Fig.11 This is a diagram showing the results of non-invasive and histological evaluation of the back skin of nude mice in the sunscreen film animal experiment of Example 11;

[0041] in, Figure 1 A is the SEM image of pure PVB fiber and the statistical diagram of fiber diameter distribution. Figure 1 B is the SEM image and fiber diameter distribution statistics of the titanium dioxide / PVB composite micro-nano fiber membrane of Example 1, Figure 1 C is the SEM image and fiber diameter distribution statistical diagram of the Enteromorpha polysaccharide composite sunscreen film of Example 1; Figure 2 A to 2C are the initial contact angle test results. Figure 2 A is the contact angle test result of pure PVB fiber film. Figure 2 B is the contact angle test result of titanium dioxide / PVB composite micro-nano fiber membrane. Figure 2 C is the contact angle test result of the sunscreen film. Figure 2 D to 2F are the contact angle test results measured after 3 minutes of liquid infiltration. Figure 2 D is the contact angle test result of pure PVB fiber film. Figure 2 E is the contact angle test result of titanium dioxide / PVB composite micro-nano fiber membrane. Figure 2 F is the contact angle test result diagram of the sunscreen film; Figure 5 A is the fluorescent in vivo imaging photo of Example 6, Figure 5 B is the curve of fluorescence intensity changing with time; Figure 6 A is an optical microscope photo of the skin surface before covering with sunscreen film. Figure 6 B is an optical microscope photo of the skin surface covered with sunscreen film. Figure 6 C is an optical microscope photo of the skin surface after removing the sunscreen film; Fig. 9 A is the live-dead staining result of HUVEC cells. Fig. 9 B is the statistical diagram of HUVEC cell viability. Fig. 9 C is the live-dead staining result of 3T3 cells. Fig. 9 D is a statistical graph of 3T3 cell viability; Fig.10 A is a comparison of photos of the back of nude mice. Fig.10 B. Curve of skin erythema damage degree changing with time. Fig.10 C. Curve of skin infiltration damage degree changing with time; Fig.10D. Curve of skin scaling damage degree changing with time; Fig.11 A is the positive area density statistical graph, Fig.11 B is the statistical chart of collagen area percentage. Fig.11 C is the statistical chart of dermis thickness. Fig.11 D is the He staining result. Fig.11 E is the Masson staining result DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] A method for preparing a Enteromorpha polysaccharide composite sunscreen film comprises the following steps:

[0044] S1: preparing a nano spray solution containing Enteromorpha polysaccharide and a spinning solution containing nano titanium dioxide particles and PVB respectively;

[0045] S2: Spraying the nano spray solution onto the skin surface requiring sun protection care through the nano spray device;

[0046] S3: The titanium dioxide / PVB composite micro-nano fiber membrane is in situ electrospun on the skin surface sprayed with the nano spray solution through an in situ electrospinning device. The titanium dioxide / PVB composite micro-nano fiber membrane is composited with Enteromorpha polysaccharide on the skin surface to form Enteromorpha polysaccharide composite sunscreen film.

[0047] Wherein, in step S1, the nano spray solution is an aqueous solution of Enteromorpha polysaccharide, and the content of Enteromorpha polysaccharide in the aqueous solution of Enteromorpha polysaccharide is 30mg / ml; the solvent for making the spinning solution includes anhydrous ethanol, and each 10g of the spinning solution contains 0.5-1.0g of PVB and 0.025-0.1g of nano-grade titanium dioxide. Specifically, in step S1, the preparation method of the spinning solution is: dissolving PVB in anhydrous ethanol, stirring well at room temperature to obtain a PVB solution, then adding nano-grade titanium dioxide to the PVB solution, stirring well at room temperature, and ultrasonically treating to remove bubbles in the solution to obtain a spinning solution.

[0048] The nano spray device used in step S2 is an electrostatic spray device, the distance between the nozzle of the electrostatic spray device and the skin is set at 10-20 cm, the spray voltage is 5-20 kV, and the spray time is 100-130 s.

[0049] Wherein, in step S3, the distance between the spinning nozzle and the skin is 10-30 cm, the spinning voltage is 5-20 kV, and the spinning time is 200-300 s.

[0050] The average fiber diameter of the Enteromorpha polysaccharide composite sunscreen film prepared by the preparation method is 500±5.8nm, the contact angle between the sunscreen film and the liquid is greater than 100°, the tensile strength of the sunscreen film is 1.3-1.8MPa. The air permeability of the sunscreen film is ≥60mm / s, the ultraviolet blocking rate of the sunscreen film is 55-60%, and the ultraviolet blocking rate is maintained at 53-68% after soaking, and after ultraviolet irradiation for 1h, the ultraviolet blocking efficiency of the sunscreen film is consistent with that before irradiation.

[0051] The present invention will be further described below in conjunction with specific embodiments. The raw materials and reagents used in the following embodiments are:

[0052] Polyvinyl butyral (PVB): MW.90,000-120,000, Macklin;

[0053] Enteromorpha polysaccharide: purchased from Qingdao Haida Biotechnology Group (Qingdao, China), purity 95%;

[0054] Example 1

[0055] A method for preparing a Enteromorpha polysaccharide composite sunscreen film comprises the following steps:

[0056] S1: 0.7 g PVB was dissolved in 9.3 g anhydrous ethanol, stirred at room temperature for 2 h to obtain a PVB solution, and then 0.1 g nano titanium dioxide particles were added to 10 g PVB solution, stirred at room temperature for 2 h, and ultrasonically treated for 10 min to remove bubbles to obtain a spinning solution; Enteromorpha polysaccharide was dissolved in deionized water at a concentration of 30 mg / ml, and stirred for 30 min to obtain a nano spray solution;

[0057] S2: Add the nano spray solution into an electrostatic spray device, and spray the nano spray solution onto the skin surface that needs sun protection care through the electrostatic spray device. The distance between the nozzle of the electrostatic spray device and the skin is set at 10 cm, the spray voltage is 15 kV, and the spray time is 120 s.

[0058] S3: Add the spinning solution into the electrospinning device, and in situ electrospin the titanium dioxide / PVB composite micro-nano fiber membrane (morphology as shown in FIG. 1 ) on the skin surface sprayed with the nano spray solution through the in situ electrospinning device. Figure 1 B), the distance between the spinning nozzle and the skin is 15 cm, the spinning voltage is 10 kV, and the spinning time is 300 s. The titanium dioxide / PVB composite micro-nano fiber film is composited with Enteromorpha polysaccharide on the skin surface to form an Enteromorpha polysaccharide composite sunscreen film (morphology as shown in Figure 1 C).

[0059] Example 2

[0060] A method for preparing a Enteromorpha polysaccharide composite sunscreen film comprises the following steps:

[0061] S1: 1.0 g of PVB was dissolved in 9.0 g of anhydrous ethanol, and stirred at room temperature for 1.5 h to obtain a PVB solution. 0.025 g of nano-titanium dioxide particles was added to 10 g of the PVB solution, and stirred at room temperature for 1.5 h. Ultrasonic treatment was performed for 15 min to remove bubbles to obtain a spinning solution. Enteromorpha polysaccharide was dissolved in deionized water at a concentration of 25 mg / ml, and stirred for 20 min to obtain a nano-spray solution.

[0062] S2: Add the nano spray solution to the electrostatic spray device, and spray the nano spray solution onto the skin surface that needs sun protection care through the electrostatic spray device. The distance between the nozzle of the electrostatic spray device and the skin is set at 15 cm, the spray voltage is 5 kV, and the spray time is 100 s.

[0063] S3: Add the spinning solution into the electrospinning device, and use the in situ electrospinning device to in situ electrospin the titanium dioxide / PVB composite micro-nano fiber membrane on the skin surface sprayed with the nano spray solution. The distance between the spinning nozzle and the skin is 10 cm, the spinning voltage is 5 kV, and the spinning time is 200 s. The titanium dioxide / PVB composite micro-nano fiber membrane is composited with Enteromorpha polysaccharide on the skin surface, thereby forming the Enteromorpha polysaccharide composite sunscreen film.

[0064] Example 3

[0065] A method for preparing a Enteromorpha polysaccharide composite sunscreen film comprises the following steps:

[0066] S1: 0.5 g of PVB was dissolved in 9.5 g of anhydrous ethanol, and stirred at room temperature for 1 h to obtain a PVB solution. Then, 0.05 g of nano-titanium dioxide particles were added to 10 g of the PVB solution, and stirred at room temperature for 1 h. Ultrasonic treatment was performed for 20 min to remove bubbles to obtain a spinning solution. Enteromorpha polysaccharide was dissolved in deionized water at a concentration of 50 mg / ml, and stirred for 30 min to obtain a nano-spray solution.

[0067] S2: Add the nano spray solution into an electrostatic spray device, and spray the nano spray solution onto the skin surface that needs sun protection care through the electrostatic spray device. The distance between the nozzle of the electrostatic spray device and the skin is set at 20 cm, the spray voltage is 20 kV, and the spray time is 130 s.

[0068] S3: Add the spinning solution into the electrospinning device, and use the in situ electrospinning device to in situ electrospin the titanium dioxide / PVB composite micro-nano fiber membrane on the skin surface sprayed with the nano spray solution. The distance between the spinning nozzle and the skin is 30 cm, the spinning voltage is 20 kV, and the spinning time is 250 s. The titanium dioxide / PVB composite micro-nano fiber membrane is composited with Enteromorpha polysaccharide on the skin surface, thereby forming the Enteromorpha polysaccharide composite sunscreen film.

[0069] Example 4 Morphology Analysis

[0070] The morphology of the nanofiber membrane prepared in Example 1 and the pure PVB fiber membrane formed by electrospinning the PVB solution of Example 1 using the same spinning parameters as Example 1 were observed using a desktop scanning electron microscope (SEM, Phenom Pro G6, ThermoFisher). A total of 50 randomly selected fibers were used to measure the diameter distribution using image analysis software (Nano Measurer 1.2). The experimental results are shown in Figure 2. Figure 1 shown.

[0071] like Figure 1 As shown, the pure PVB fiber membrane ( Figure 1 A), titanium dioxide / PVB composite micro-nano fiber membrane ( Figure 1 B) Enteromorpha polysaccharide composite sunscreen film ( Figure 1 C) The surface morphology of the three electrospun fiber membranes was characterized. It can be seen that the fiber diameter of the pure PVB fiber membrane is about 530nm, while the fiber diameter of the titanium dioxide / PVB composite micro-nano fiber membrane is reduced to about 470nm, and the fiber diameter of the Enteromorpha polysaccharide composite sunscreen film is about 500nm. Figure 1 As shown in Figure C, we found that the addition of nano-sized titanium dioxide increased the solution conductivity from 2.6μS / cm to 13.8μS / cm. This change played a key role in the electrospinning process because the increase in conductivity effectively promoted the stretching degree of the spinning solution, thereby making the jet more refined, and finally obtaining a fiber with a finer diameter. Spraying Enteromorpha polysaccharide onto the fiber surface through nanospray increases the average diameter of the fiber to a certain extent. This is due to the attachment and accumulation of Enteromorpha polysaccharide on the fiber surface, which also proves that the preparation method of the present invention realizes the composite of Enteromorpha polysaccharide and titanium dioxide / PVB composite micro-nano fiber membrane.

[0072] Example 5 Physical Properties Test

[0073] The hydrophobicity of the pure PVB fiber film prepared in Example 4, the titanium dioxide / PVB composite micro-nano fiber film and the sunscreen film prepared in Example 1 was tested using a contact angle meter (Theta, Biolin Scientific, Sweden) and 2 μl (cola, Sprite, sparkling water, black tea, water) droplets. The experimental results are shown in Figure 2. Figure 2 The stress-strain test was carried out by using a universal material testing machine (Instron 5300, USA). The fiber membrane was cut into a size of 10 mm × 20 mm and stretched at a tensile rate of 20 mm / min. The test results are shown in Figure 3 Using a gas permeability analyzer (FX3300IV, Switzerland), at a constant pressure of 200 Pa, the preparation area of ​​20cm 2 The air permeability of the nanofiber sunscreen film was tested. The test results are as follows Figure 4 shown.

[0074] The skeleton of nanofiber sunscreen film, PVB, is a hydrophobic material. The hydrophobic principle mainly comes from the non-polar hydrocarbon groups in its molecular structure. These groups make PVB hydrophobic as a whole. The roughness of the PVB surface and the interaction with other substances (such as chemical reactions or the formation of special nanostructures) may further enhance its hydrophobic properties. These factors work together to make PVB and its composite materials show excellent hydrophobic properties in a variety of applications. Figure 2 As shown in A to F, this study systematically analyzed the contact behaviors of three nanofiber sunscreen films with five liquids that are easily contacted in daily life (cola, Sprite, sparkling water, black tea and water). Figure 2 As shown in A to C, at the initial contact stage, the contact angles between these nanofiber sunscreen films and liquids are all over 100°, indicating excellent hydrophobic properties. Figure 2 As shown in D to F, after three minutes of static observation, the contact angle of these nanofiber sunscreen films is still maintained above 100°, which fully verifies that even after long-term contact with liquids, they can still maintain their stable hydrophobic properties. Since different liquids vary in chemical composition, pH, and surface tension, the contact angles are different, but they can fully reflect the hydrophobic properties of the sunscreen film in different liquid environments. Sunscreen films with excellent hydrophobic properties can effectively prevent the sunscreen film from being eroded by water or daily contact liquids, thereby ensuring the long-lasting and stable sunscreen effect.

[0075] like Figure 3As shown, the addition of nano-titanium dioxide and the compound of Enteromorpha polysaccharide have a slight effect on the mechanical properties of the fiber membrane, but the tensile stress of the three fiber membranes is between 1.3MPa and 1.8MPa, which meets the tensile strength requirements of human skin. The sunscreen film of Example 1 exhibits excellent tensile properties, and its Young's modulus is similar to that of human skin. This feature enables the sunscreen film to adapt more closely to human skin in practical applications, reducing the feeling of tightness or restraint that may be caused by excessive rigidity of the material, thereby greatly improving the wearer's comfort experience.

[0076] like Figure 4 As shown in the figure, under the constant pressure test condition of 200Pa, the air permeability of the nanofiber sunscreen film was systematically evaluated. The results showed that pure PVB had the best air permeability, with an air permeability rate of 71.5mm / s. After adding nano-sized titanium dioxide, the air permeability rate slightly decreased to 70mm / s. After compounding Enteromorpha polysaccharide, the air permeability rate slightly decreased to 65.4mm / s, all of which had excellent air permeability. This excellent air permeability is attributed to the unique structural characteristics of nanofibers. Nanofibers construct a complex and orderly pore structure through interweaving and lateral connection, which gives the nanofiber film an extremely high porosity. This high porosity allows air molecules to easily pass through the fiber membrane, thereby achieving good air permeability. This property is particularly critical in the application of sunscreen products. While maintaining waterproof properties, the nanofiber sunscreen film can effectively discharge moisture from the body, thereby preventing the stuffiness caused by moisture accumulation.

[0077] Example 6 Skin Adhesion Test

[0078] Rhodamine B was pre-dissolved in the spinning solution, and the labeled spinning solution was in situ electrospun on the dorsal skin of nude mice. The back of the nude mice was cleaned with ethanol before the experiment and placed in an anesthetized state. The sunscreen film was applied to the skin of the nude mice using the preparation method of Example 1. At specific time points (0, 30, 60 and 120 min), the fluorescence of the dorsal skin was measured using real-time imaging technology to determine the retention of the nanofiber sunscreen film on the dorsal skin, so as to evaluate the skin adhesion of the sunscreen film on the dorsal skin. The experimental results are shown in FIG. Figure 5 shown.

[0079] like Figure 5As shown, through in-situ electrospinning precise deposition, a close fit between the nanofiber membrane and the skin of nude mice was observed. In subsequent observations, we recorded in detail the dynamic data of the fluorescence intensity of the nanofiber membrane over time. The data showed that although the fluorescence intensity showed a certain degree of attenuation over time, after 120 minutes, its fluorescence intensity still maintained a high level of more than 80%. This result strongly proves that the sunscreen film of the present invention has excellent skin adhesion properties. This is because the charges generated during the in-situ electrospinning process contribute to the electrostatic adsorption between the nanofibers and the skin, enhancing the adhesion effect. Secondly, the diameter of the nanofibers is usually very small, and can form a microscopic concave-convex structure on the skin surface. This structure can increase the friction between the skin and the nanofibers, thereby improving the adhesion.

[0080] Example 7 Removal Test Results

[0081] By testing the removability of the sunscreen film, it can be ensured that the product is easy to remove, reducing the potential risks of pore blockage, and then causing acne, pimples, etc. The sunscreen film was prepared on a piece of pig skin (35*35mm) using the preparation method of Example 1. After 1 minute, the sunscreen film was gently rubbed off the pig skin by hand. An optical microscope (IX53, Olympus, Japan) was used to observe the morphological characteristics of the pig skin before applying the sunscreen film (bare pig skin), after applying the sunscreen film (sunscreen layer on pig skin), and after removing the sunscreen film coating. The results are as follows: Figure 6 shown.

[0082] In the test of the removability of the sunscreen film, we chose pigskin as the experimental model due to its similarity to human skin, so as to obtain test results that are closer to the actual human body. After gently rubbing the sunscreen film off the pigskin with hands, the surface of the pigskin was no longer obviously covered with the sunscreen film under naked eye observation. In order to ensure the accuracy and reliability of the results, we conducted a detailed analysis under a microscope. The results are as follows Figure 6 As shown, even under magnified observation, no residue of the nanofiber sunscreen film is left on the surface of the pig skin. This excellent removability is due to the unique adhesion mechanism of the sunscreen film of the present invention. It mainly forms a non-permanent, interconnected solid structure with the skin surface through van der Waals forces. This structure enables the nanofiber sunscreen film to fit closely to the skin when needed, providing long-lasting and effective sun protection; at the same time, when it needs to be removed, it can be easily peeled off from the skin surface without leaving any trace. Therefore, for those who are particularly sensitive to the chemicals that may remain in traditional sunscreens, the sunscreen film of the present invention undoubtedly provides a safe and effective alternative. It can not only meet their needs for sun protection effects, but also effectively avoid the residue problems that may be caused by traditional sunscreen films, allowing the skin to maintain a healthy and comfortable state while enjoying the sun.

[0083] Example 8 UV blocking rate test

[0084] The UV transmittance of the pure PVB fiber film prepared in Example 4, the titanium dioxide / PVB composite micro-nano fiber film (PVB-TiO2) of Example 1, the sunscreen film (PVB-TiO2-EPPs), the PVB-TiO2-EPPs treated with 365nm ultraviolet irradiation, and the PVB-TiO2-EPPs with a water-infiltrated surface layer was measured at a wavelength of 240nm to 400nm at intervals of 1nm using a diffuse reflectance UV-Visible / NIR Spectrophotometer (UH4150, Japan); the UV transmittance was measured at four points of each sample, and the average value was used. The test results are shown in FIG. Figure 7 shown.

[0085] The ultraviolet band from 240nm to 400nm mainly includes medium-wave ultraviolet rays and long-wave ultraviolet rays, which are harmful to the human body. Figure 7 As shown, in the 240nm to 400nm band, the UV blocking rate of pure PVB is between 55% and 60%, and this efficiency shows a slight downward trend as the wavelength increases. When nano-TiO2 is introduced into the PVB matrix, the UV blocking performance is significantly enhanced. Especially in the medium-wave UV region of 240nm to 330nm, this is mainly because nano-TiO2 has a strong absorption of medium-wave UV, and mainly blocks UV in the form of absorption. However, in the long-wave UV region of 330nm to 400nm, although the blocking effect is weakened compared to the medium-wave region, its UV blocking performance is still significantly improved compared to pure PVB. The UV blocking rate of PVB-TiO2-EPPs shows that Enteromorpha polysaccharide has little effect on the basic UV blocking rate.

[0086] like Figure 7 As shown in the figure, after testing the PVB-TiO2-EPPs nanofiber sunscreen film under 365nm ultraviolet radiation for 1h, the results showed that its UV blocking rate was basically the same as before irradiation, with only a slight decrease observed. This result shows that the sunscreen film has excellent light stability. In addition, in order to evaluate the water stability of the PVB-TiO2-EPPs nanofiber sunscreen film, we soaked its fiber film in water for 5min. The test results showed that its UV blocking rate only decreased by about 2%. This slight change further verified the stability of the sunscreen film in a water environment. The UV protection performance of traditional sunscreen films tends to decrease significantly when exposed to water or sweat, thus limiting its effectiveness in practical applications. However, the PVB-TiO2-EPPs nanofiber sunscreen film can maintain a high UV blocking rate while maintaining water stability.

[0087] Example 9 Particulate matter barrier efficiency test

[0088] The fine particle blocking efficiency of nanofiber sunscreen film and N95 mask was tested by PALAS MFP3000 filter material test bench. The effective area used in the test was 100cm 2 The dust generator disperses the 10% KCl solution into tens of thousands of particles of different sizes. These solid KCl particles are sent to the test filter by the atomizer through the air pump at a pre-designed air flow rate (20cm / s). The average diameter of the particles ranges from 0.225 to 10 microns. In order to evaluate the filtration efficiency of the filter, two laser particle counters are used to measure the number of particles upstream and downstream of the filter respectively; at the same time, a differential pressure sensor is used to measure the pressure difference on both sides of the filter to evaluate the pressure drop of the filter. The experimental results are as follows: Figure 8 shown.

[0089] PM2.5 can enter the skin through the pores. When PM2.5 accumulates more and more on the skin, it will clog the pores, sebaceous gland ducts and hair follicles, affect the normal metabolism of the skin, and induce skin problems such as acne, blackheads, and pimples. Figure 8 As shown in the figure, the PVB-TiO2-EPPs nanofiber sunscreen film prepared in this study has excellent performance in PM1.0 filtration efficiency. Compared with the widely recognized N95 mask, both can achieve a filtration efficiency of more than 99%. However, when comparing the pressure drop data of the two, we observed that the nanofiber sunscreen film showed a lower pressure drop value (115Pa), which is significantly lower than the 205Pa of the N95 mask. This data shows that while maintaining excellent filtration performance, the nanofiber sunscreen film also has better air permeability than the N95 mask.

[0090] Example 10 Cytocompatibility Experiment

[0091] 10.1 Cell seeding, culture and characterization

[0092] First, human umbilical vein endothelial cells (HUVEC, Chinese Academy of Sciences Cell Membrane, China) and mouse embryonic fibroblasts (NIH-3T3, Chinese Academy of Sciences Cell Membrane, China) were cultured in GIBCO high glucose DMEM complete medium. The culture medium contained 10% (v / v) fetal bovine serum (FBS) and penicillin / streptomycin (PS) (1%). They were divided into four groups (control, PVB (Example 4), PVB-TiO2 (Example 1), PVB-TiO2-EPP (Example 1)), and then the above materials were placed in a 5% concentration C2 incubator at 37°C under sterile conditions for co-culture, and the cell culture medium was replaced regularly. When the cell growth density reached 80-90%, the cells (at a cell density of 1×104) were inoculated into a 96-well plate after digestion with trypsin.

[0093] On days 1, 3, and 7 of co-culture, cell counting kit-8 (CCK-8) was used to evaluate the cell viability and proliferation of human umbilical vein endothelial cells (HUVEC) and mouse embryonic fibroblasts (NIH-3T3). The specific operation was as follows: the corresponding 96-well cell culture plate was removed from the incubator, the old culture medium and materials were discarded, and the plate was washed three times with phosphate buffered saline (PBS). 100 μl of fresh complete culture medium and 10 μl of CCK-8 reagent were added to each well under light-proof conditions. After incubating the 96-well cell culture plate in a humid atmosphere of 5% CO2 at 37°C for 2 hours in the dark, the 96-well cell culture plate was removed, 80 μl of the incubated liquid in the well was transferred to a new 96-well cell culture plate, and the absorbance (OD) of each well at 450 nm was measured by a microplate reader. The OD values ​​were measured in the same way on days 3 and 7. The OD values ​​of the three days were summarized and the changes of OD values ​​over time were plotted.

[0094] The cell viability calculation formula is as follows: cell viability (%) = (experimental group / blank control) × 100%.

[0095] 10.2 Cell viability and live / dead staining

[0096] This example uses a live / dead cell viability assay kit (Yeasen Biotechnology (Shanghai)) to measure cell viability. Calcein AM is used to label live cells, while propidium iodide (PI) is used to label dead cells. Live cells appear green, while dead cells appear red.

[0097] First, take out the Calcein AM Solution and PI Solution, balance at room temperature for 30 minutes, then add 5μl of PI Solution and 5μl of Calcein AM Solution to 10ml of PBS, vortex and shake evenly to make a working solution (the concentration of Calcein AM is 2μm and the concentration of PI is 8μm). Then stain human umbilical vein endothelial cells (HUVEC) and mouse embryonic fibroblasts (NIH-3T3). Then use a high-speed centrifuge (Meng'an Instrument Equipment Co., Ltd. (Jiangsu)) to centrifuge and collect cells (104-105 cells) at 1,000rpm for 3min. After centrifugation, remove the supernatant and wash with PBS 2-3 times to ensure that the active esterase contained in the culture medium is removed. Then use 100μl of staining working solution to stain human umbilical vein endothelial cells (HUVEC) and mouse embryonic fibroblasts (NIH-3T3) and incubate at 37℃ for 15-30min.

[0098] Add an appropriate amount of stained cell solution on a clean glass slide and cover it with a coverslip. It can be sealed with nail polish to prevent water evaporation. Live cells (yellow-green fluorescence) and dead cells (red fluorescence) are observed simultaneously under a Zeiss fluorescence microscope (Aono Optical Technology Co., Ltd. (Shenzhen)) using an excitation wavelength of 490±10nm. In addition, dead cells are observed separately using an excitation wavelength of 545nm. ImageJ software was used to quantify live and dead cells after 24 hours of exposure to PVB, PVB-TiO2, and PVB-TiO2-EPP eluents. The data report takes the average of three results.

[0099] The experimental results are as follows Fig. 9 As shown in the figure, HUVEC cells (human umbilical vein endothelial cells) and 3T3 cells (mouse embryonic fibroblasts) are commonly used cell models, representing vascular endothelial cells and fibroblasts, respectively, and can simulate the potential effects of sunscreen films on skin blood vessels and interstitial tissues. Therefore, using these two cells to test the cell compatibility of sunscreen films can more comprehensively evaluate the potential effects of sunscreen films on skin cells. Fig. 9 As shown, after adding PVB, PVB-TiO2, and PVB-TiO2-EPPs, there was no significant difference in cell viability compared with the control group, indicating that the nanofiber sunscreen film has good biocompatibility.

[0100] Example 11 Skin sunscreen efficacy experiment

[0101] All animal experiments were performed in accordance with the experimental animal protocol approved by the Ethics Committee of Qingdao University and the relevant laws and guidelines of Qingdao University. Female BALB / c nude mice (8 weeks old) with an average initial weight of 200 g were purchased from Sibeifu (Beijing) Biotechnology Co., Ltd. The nude mice were housed in an SPF-grade animal room and fed with sterile diet and water for one week of adaptive feeding under special pathogen-free conditions. Then the nude mice were randomly divided into four groups (blank control group, UV irradiation group, PVB-TiO2 + UV irradiation group (PVB-TiO2 fiber membrane was prepared on the skin of nude mice according to the method of Example 1, and step S2 was omitted in the preparation process), PVB-TiO2-EPPs + UV irradiation group (PVB-TiO2-EPPs fiber membrane was prepared on the skin of nude mice according to the method of Example 1, i.e., the sunscreen film of Example 1), 4 mice in each group, and a 4-day anti-ultraviolet evaluation experiment was carried out. Briefly, the mice were anesthetized and their back skin was cleaned with 75% alcohol, and then the dorsal epidermis of these mice was treated differently. The mice were placed at an irradiation height of 12 cm, an irradiation area of ​​2 cm×3 cm, an ultraviolet irradiation intensity of 1.00 mW cm-2, and a single ultraviolet irradiation dose of 600 mJ cm-2; irradiation was continued for 4 days, and the total ultraviolet irradiation dose was 2400 mJ cm-2. Before and after irradiation, photos were taken to observe the skin condition of nude mice in each group and the relevant indicators were scored (the scoring criteria are shown in the following table). After the last drug intervention and UV irradiation, the nude mice in each group were killed, and the skin tissues of nude mice were taken for HE, Masson, and immunohistochemistry (COX-2) staining to evaluate the skin pathology of nude mice in each group.

[0102] The scoring criteria for back skin erythema, infiltration and scaling in skin lesions are as follows:

[0103]

[0104] Test results see Figure 10 to Figure 11 Among them, the UV shielding performance of the sunscreen film is as follows Fig.10 As shown, Fig.10A is to take photos and record the back skin of nude mice every day. On the first day of UV irradiation, it was observed that the back skin of nude mice in the PVB-TiO2 UV irradiation group and the UVB group showed mild erythema, indicating that both groups were slightly affected by ultraviolet rays. At the same time, the skin of nude mice in the blank control group and the PVB-TiO2-EPPs UV irradiation group remained natural flesh color without obvious changes. On the second day, the erythema phenomenon on the skin of nude mice in the UVB group was significantly aggravated, showing the cumulative effect of ultraviolet damage to the skin. In contrast, the degree of erythema in the PVB-TiO2 UV irradiation group remained mild, while the PVB-TiO2-EPPs UV irradiation group continued to maintain a healthy state of skin, and no erythema or other abnormal changes were observed. On the third day, the erythema in the UVB group further worsened, showing signs of gradual darkening, which may be due to pigmentation caused by severe skin damage. Although the PVB-TiO2 UV irradiation group still maintained mild erythema, there was no significant change compared with the previous two days. The PVB-TiO2-EPPs UV irradiation group continued to maintain a healthy skin condition. On the fourth day, the erythema and pigmentation of the UVB group became more serious, showing that ultraviolet rays continued to cause serious damage to the skin. Although the degree of erythema in the PVB-TiO2 UV irradiation group remained mild, there was no obvious relief compared to the previous few days. The skin condition of the PVB-TiO2-EPPs UV irradiation group was still healthy. In addition, the skin of the blank control group remained healthy flesh color throughout the experiment. No infiltration or scaling reaction occurred during the four animal experiments. It can be seen that the sunscreen film (PVB-TiO2-EPPs) of this embodiment can achieve better sun protection effect.

[0105] The skin barrier function of nude mice was measured daily by noninvasive assessment before artificial intervention and UVB irradiation. Erythema, scaling, and infiltration are usually key parameters for evaluating UV-related skin damage. Before the experiment, erythema, scaling, and infiltration were scored independently every day using a semiquantitative scoring scale (0-4). Fig.10 B to D are the test results of erythema, infiltration, and scaling, respectively. In the UV irradiation group, it was observed that these scores increased significantly from 0 to 3-4 in the first four days, indicating that the acute light damage model was successfully established. Under UV irradiation conditions, the score of the PVB-TiO2 nanofiber sunscreen film experimental group remained at 1 point, indicating that the PVB-TiO2 nanofiber sunscreen film has a good sun protection effect, but there is still some skin damage to a certain extent, and there is room for improvement. In contrast, the PVB-TiO2-EPPs nanofiber sunscreen film experimental group continued to show an excellent score of 0 points, which is significantly better than the PVB-TiO2 group, fully proving its excellent protection against skin damage and highlighting the protective effect of the spraying of Enteromorpha polysaccharide on the skin.

[0106] Non-invasive and histological evaluation of the back skin Fig.11 As shown, Fig.11 C shows that at the end of the experiment, the skin of the nude mice back (1cm×1cm) was collected and the thickness was measured using a vernier caliper. The average thickness of the normal skin in the control group without any treatment was 180.47mm. However, after high-dose UVB irradiation, the skin of the UV-irradiated group became significantly thinner, with a thickness of about 117.52.um. This is because ultraviolet rays can destroy collagen and elastic fibers in the skin (see Fig.11 A and Fig.11 B), which are important components for maintaining skin thickness and elasticity. The normal structure of the skin is destroyed and the skin becomes thinner. After the intervention treatment of PVB-TiO2 nanofiber sunscreen film and PVB-TiO2-EPPs nanofiber sunscreen film, the skin thickness was 143.15μm and 154.14μm, respectively, which was significantly better than the UVB group (*****P<0.005). The results confirmed that PVB-TiO2 nanofiber sunscreen film and PVB-TiO2-EPPs nanofiber sunscreen film effectively inhibited UVB from thinning the skin. At the same time, it can be seen that the sunscreen film of this embodiment (PVB-TiO2-EPPs nanofiber sunscreen film) is more effective than PVB-TiO2 nanofiber film. This should be attributed to the fact that Enteromorpha polysaccharide, as an antioxidant, can eliminate free radicals generated by the photocatalytic action of TiO2, and stimulate the skin's self-repair ability, promote the regeneration and repair of damaged skin cells, which is very beneficial for resisting skin damage and aging caused by ultraviolet rays.

[0107] like Fig.11 As shown in D, histological sections of the back skin tissue were stained with hematoxylin and eosin to observe the damage to the epidermis and dermis. In the blank control group, regular stratum corneum, epidermis, and orderly arranged fibers in the dermis were observed. However, the dermis in the UV irradiation group became thinner, and the number of collagen fibers decreased and was loosely arranged. Compared with the UV irradiation group, the dermis thickness increased and the number of sebaceous sweat glands increased in the PVB-TiO2 group and the PVB-TiO2-EPPs group, and their structure was similar to that of normal skin. In addition, immunohistological staining showed that COX-2 was overexpressed after UVB irradiation (UVB group) and the positive area in the PVB-TiO2-EPPs group was significantly reduced (see Fig.11 D). Both histopathological and immunohistochemical analyses confirmed that the PVB-TiO2-EPPs group exhibited excellent protective properties against UV-induced damage.

[0108] Masson trichrome staining is also used to evaluate the UV protection of sunscreen films. Fig.11As shown in E, the collagen fibers in the skin of the blank control group are wavy, uniform in thickness, moderate in thickness, and closely arranged, which reflects the healthy state of normal skin tissue. The number of collagen fibers in the UVB group is reduced, and the fractures are discontinuous. The fiber diameter becomes thinner, the arrangement is loose and disordered, and the gaps are widened. These changes indicate that UVB irradiation has caused significant damage to the skin collagen fibers. Compared with the UVB group, the number of collagen fibers in the PVB-TiO2 group and the PVB-TiO2-EPPs group increases, the diameter thickens, and the arrangement is more neat and tight. From the experimental results, it can be seen that the collagen fiber content of the skin after the treatment of the PVB-TiO2-EPPs group is closer to that of the blank control group, indicating that the sunscreen film of this embodiment has more significant efficacy in resisting UVB damage.

[0109] The above experiments prove that the sunscreen film prepared by the preparation method of this embodiment has excellent physical properties, high cell compatibility, air permeability, hydrophobicity, and tensile properties. After continuous ultraviolet light irradiation, the ultraviolet blocking efficiency of the sunscreen film can be consistent with that before irradiation, showing excellent light stability. In addition, after being soaked in water, the ultraviolet blocking efficiency only decreases by about 2%, and has good water stability. The sunscreen film can still maintain more than 80% adhesion after being applied to the skin for a long time, and is easy to remove without residue, effectively avoiding pore blockage and skin irritation problems.

[0110] The above description is only an example of the present invention and is not intended to limit the present invention in other forms. Any technician familiar with the profession may use the technical contents disclosed above to change or modify them into equivalent embodiments with equivalent changes and apply them to other fields. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the technical solution content of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a Enteromorpha polysaccharide composite sunscreen film, characterized in that: The following steps are involved: S1: preparing a nano spray solution containing Enteromorpha polysaccharide and a spinning solution containing nano titanium dioxide particles and PVB respectively; S2: Spray the nano spray solution onto the skin surface that needs sun protection care through the nano spray device: S3: The titanium dioxide / PVB composite micro-nano fiber membrane is in situ electrospun on the skin surface sprayed with the nano spray solution through an in situ electrospinning device. The titanium dioxide / PVB composite micro-nano fiber membrane is composited with Enteromorpha polysaccharide on the skin surface to form Enteromorpha polysaccharide composite sunscreen film.

2. The preparation method according to claim 1, characterized in that: In step S1, the nano spray solution is an aqueous solution of Enteromorpha polysaccharide, and the content of Enteromorpha polysaccharide in the aqueous solution is 25-50 mg / ml; the solvent for making the spinning solution includes anhydrous ethanol, and each 10g of the spinning solution contains 0.5-1.0g of PVB and 0.025-0.1g of nano-grade titanium dioxide.

3. The preparation method according to claim 2, characterized in that: In step S1, the spinning solution is prepared by: dissolving PVB in anhydrous ethanol, stirring the solution at room temperature to obtain a PVB solution, adding nano-sized titanium dioxide to the PVB solution, stirring the solution at room temperature to obtain a spinning solution.

4. The preparation method according to claim 3, characterized in that: Step S1 comprises: dissolving 0.5-1.0 g of PVB in 9.0-10.0 g of anhydrous ethanol, stirring at room temperature for 1-2 hours to obtain a PVB solution, adding 0.025-0.1 g of nano titanium dioxide particles to 10 g of the PVB solution, stirring at room temperature for 1-2 hours, and ultrasonically treating for 10-20 minutes to remove bubbles to obtain a spinning solution; dissolving Enteromorpha polysaccharide in deionized water at a concentration of 25-50 mg / ml, and stirring for 10-30 minutes to obtain a nano spray solution.

5. The preparation method according to claim 1, characterized in that: The nano spray device used in step S2 is an electrostatic spray device, the distance between the nozzle of the electrostatic spray device and the skin is set at 10-20 cm, the spray voltage is 5-20 kV, and the spray time is 100-130 s.

6. The preparation method according to claim 1, characterized in that: In step S3, the distance between the spinning nozzle and the skin is 10-30 cm, the spinning voltage is 5-20 kV, and the spinning time is 200-300 s.

7. A Enteromorpha polysaccharide composite sunscreen film, characterized in that: The method is prepared according to any one of claims 1 to 6.

8. The sunscreen film according to claim 7, characterized in that: The average fiber diameter of the sunscreen film is 500±5.8nm.

9. The sunscreen film according to claim 7, characterized in that: The contact angle between the sunscreen film and the liquid is greater than 100°; the tensile strength of the sunscreen film is 1.3-1.8MPa; the air permeability of the sunscreen film is ≥60mm / s; the UV blocking rate of the sunscreen film is 55-60%, and the UV blocking rate remains at 53-68% after soaking, and after 1 hour of UV irradiation, the UV blocking efficiency of the sunscreen film remains the same as before irradiation; After being loaded in situ on the skin for 120 minutes, the sunscreen film can still maintain more than 80% of its adhesion.

10. Use of the sunscreen film as claimed in claim 7 in the field of skin sun protection.

Citation Information

Patent Citations

  • Titanium dioxide / algal polysaccharide composite nanometer particles and preparation method and application thereof

    CN107582422A

  • Method for producing ultraviolet protection coating film

    CN110520100A

  • Sunscreen cosmetic composition for external use on skin

    CN112535646A

  • Preparation method of nano filamentous gel mask based on coaxial electrostatic spinning and product of nano filamentous gel mask

    CN113576927A

  • Nanofiber mask with multi-component slow-release capability as well as preparation method and use method of nanofiber mask

    CN116999345A